ECO-ENZYME : LIQUID ORGANIC FERTILIZER ON THE GROWTH OF MUSTRAIN PLANTS (Brassica chinensis) AS SUPPORTING LITERACY AND NUMERATION - Tuapattinaya, Prelly M. J; Tiven, Jessica Gabriella; Fretes, Gracia de; Madubun, Gloria; Lopulalan, Gabriela (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2024)
Eco-enzyme is a mixture of organic fruit peel waste fermented with a mixture of brown sugar and water. It can be used as organic fertilizer. The aim of the research is to find out how eco-enzymes help literacy and numeracy in the growth of mustard greens (Brassica chinensis). Eco-enzymes are made with a composition of 10:3:1: 10 liters of water, 3 kilograms of vegetable waste or fruit peels, and 1 kilogram of brown sugar. In a fifteen liter plastic container, dissolve brown sugar in water. Then, add the skins and vegetable waste, and cover tightly and ferment for three months. Mustard seeds are sown and planted in polybags. Watering is done with water every day; watering with eco-enzyme solution is carried out once every three days. The amount of eco-enzyme used is 0 ml, 7.5 ml, 15 ml, and 22.5 ml in one liter of water. The parameters measured for mustard plants are height (cm) and number of leaves (sheets). The research results showed that the application of eco-enzymes as organic fertilizer at a concentration of 7.5 ml had a positive impact on the height and number of leaves of mustard plants, but had a negative impact on eco-enzyme concentrations of 15 ml and 22.5 ml. Thus, it can be concluded that administering eco-enzymes as organic fertilizer provides the most effective effect at the level of 7.5 ml